Kedudukan Bank dalam Perjanjian Kredit dengan Klausul Negative Pledge of Assets: Bank Position in Credit Agreements with Negative Pledge of Assets Clauses - Tjahjono, Monica (Warkat, 2021)
Development is one of the important pillars in the economy and business financing is one of its sources. When applying for a loan, debtors are generally required to collateralize assets to guarantee to creditors that they are able to pay off their debts. With this guarantee, a creditor becomes a separatist creditor. However, there is also the concept of negative pledge of assets, where debtors do not need to pledge their assets. However, in financing businesses, banks must always apply prudential principles, including the 5C principle, which requires collateral. This research was conducted to determine the position of creditors when bound by credit agreements that use the Negative Pledge of Assets clause, as well as to find solutions for implementing the Negative Pledge of Assets clause that can fulfill the precautionary principle. Juridical normative research is used in this research accompanied by a statutory approach and a conceptual approach. Although the Negative Pledge of Assets clause can be used in the practice of granting credit agreements, there are no regulations that specifically regulate the use of this clause. Creditors who are bound by a credit agreement with a Negative Pledge of Assets clause will become concurrent creditors and in the event of bankruptcy of the debtor, repayment of the debt will be carried out proportionally in accordance with the provisions of Article 1132 of the Civil Code. However, there are several clauses that can be used in conjunction with the Negative Pledge of Assets clause in addition to the prohibitory provisions for guaranteeing debt repayment. This clause is a clause that requires creditor permission before the debtor submits a new credit application as well as an Automatic Crystallization clause.